Euro and the financial relations between Latin America and Europe : medium- and long-term implications - Miotti, Luis (ECLAC SantiagoCL, 2002)
Evaluates the initial steps of the euro and its internationalization in general terms. Analyses the factors that will have a bearing on the internationalization of the European currency. Examines the channels through which the euro will exert an influence in Latin America on the basis of the recent development of relations between the two regions, looking at trade flows and financial flows. Makes a prospective analysis of the ways the euro can come to be used as an anchor currency in Latin America.